An Improved Water-Filling Algorithm Based On Power Allocation In Network Mimo - Mohd Kasim, Noor Shahida; Nordin, Rosdiadee; Ismail, Mahamod (Springer, 2020)
Inter-Cell Interference (ICI) could affect the performance of the LTE-Advanced (LTE-A) system and can be evaluated according to the user’s Signal to Interference and Noise Ratio (SINR). Owing to this, the power and frequency allocation schemes can be utilized in order to attain an optimum trade-off within the obtained SINR and the resulting interference. In this study, power allocation was integrated into the Dynamic Fractional Frequency Reuse (DFFR) scheme and Network MIMO (NetMIMO) to reduce ICI and enhance the performance of LTE-A downlink. Moreover, this study focuses on the design and development of a novel power allocation algorithm, which is an extension to the previous Improved Water-Filling algorithm (IWF), namely, Low-Complexity Improved Water-Filling algorithm (LC-IWF). Results indicated a reduction in computations and enhancement in interference rejection performance in comparison to the existing algorithms by removing the Lagrange multiplier and water level. Moreover, simulation results revealed that the proposed algorithm enhances the throughput and fairness of up to 20% and 25%, respectively. Furthermore, the power consumption was reduced by 41% and the running time was 5–10 times faster than the IWF algorithm while attaining the best solution. The proposed power allocation algorithm provided a significant improvement in the performance of the NetMIMO LTE-A system, which can be extended for future 5G networks.